2022
DOI: 10.1371/journal.pone.0274222
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of the rapid molecular detection of RSV and influenza A and B viruses in the emergency department

Abstract: Introduction Using respiratory virus rapid diagnostic tests in the emergency department could allow better and faster clinical management. Point-of-care PCR instruments now provide results in less than 30 minutes. The objective of this study was to assess the impact of the use of a rapid molecular diagnostic test, the cobas® Influenza A/B & RSV Assay, during the clinical management of emergency department patients. Methods Patients (adults and children) requiring admission or suffering from an underlying… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Viral testing may for some centers be something of a moving target. Point-of-care PCR has been demonstrated to improve ED care for RSV and influenza 43 . Antigen tests in general have significant performance problems unless the prevalence is high 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Viral testing may for some centers be something of a moving target. Point-of-care PCR has been demonstrated to improve ED care for RSV and influenza 43 . Antigen tests in general have significant performance problems unless the prevalence is high 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The multiplication of rapid detection methods for respiratory viruses, ranging from antigen tests [ 5 ] to rapid point-of-care multiplex PCRs [ 6 ] has allowed for a broader detection of RSV. However, this can also complicate its surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Although antigen testing can be used in infants due to its relative cost-effectiveness, this method is inaccurate in older patients [ 5 ]. Patients requiring hospitalisation should benefit from more expensive rapid multiplex PCRs to allow better clinical management and relevant hygiene precautions [ 6 ]. As shown in this study, the intertwinement of influenza, RSV and probably SARS-CoV-2 could clinically justify the systematic use of such multiplex PCRs during the epidemic season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that rapid and accurate diagnosis of respiratory infections enhances clinical management by adjusting the indications for isolation, antibiotic, and antiviral treatment due to better analytical performances than rapid diagnostic tests during seasonal IAV, IBV and RSV epidemics [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%